Cytotoxic Effects of Different Aromatic Plants Essential Oils on Oral Squamous Cell Carcinoma- an in vitro Study - Lazarević Miloš; Milošević Maja; Petrović Nada; Petrović Slobodan; Damante Giuseppe; Milašin Jelena; Milovanović Branislav (Balkan Stomatological Society, 2019)
Background/Aim: Current approaches in therapy of head and neck cancers are surgery, radiotherapy and chemotherapy. However, recurrence, development of multidrug resistance, side effects, and high costs of therapy are significant problems which point to the need for more efficient and less toxic drugs and interventions.